Livestock systems research manual. Volume 2 - International Livestock Centre for Africa (International Livestock Centre for Africa, 1990)
Discusses livestock on-farm trials by outlining the definitions, problems and initial considerations in planning livestock on-farm trials; design, implementation, monitoring and evaluation of livestock on farm trials; and analyses data from on-farm trials.